Enhanced Nrf2 Activity Worsens Insulin Resistance, Impairs Lipid Accumulation in Adipose Tissue, and Increases Hepatic Steatosis in Leptin-Deficient Mice - Xu, Jialin (American Diabetes Association, 2012)
The study herein determined the role of nuclear factor erythoid 2–related factor 2 (Nrf2) in the pathogenesis of hepatic steatosis, insulin resistance, obesity, and type 2 diabetes. Lep(ob/ob)-Keap1-knockdown (KD) mice, which have increased Nrf2 activity, were generated. Markers of obesity and type 2 diabetes were measured in C57Bl/6J, Keap1-KD, Lep(ob/ob), and Lep(ob/ob)-Keap1-KD mice. Lep(ob/ob)-Keap1-KD mice exhibited less lipid accumulation, smaller adipocytes, decreased food intake, and reduced lipogenic gene expression. Enhanced Nrf2 activity impaired insulin signaling, prolonged hyperglycemia in response to glucose challenge, and induced insulin resistance in Lep(ob/ob) background. Nrf2 augmented hepatic steatosis and increased lipid deposition in liver. Next, C57Bl/6J and Keap1-KD mice were fed a high-fat diet (HFD) to determine whether Keap1 and Nrf2 impact HFD-induced obesity. HFD-induced obesity and lipid accumulation in white adipose tissue was decreased in Keap1-KD mice. Nrf2 activation via Keap1-KD or sulforaphane suppressed hormone-induced differentiation and decreased peroxisome proliferator–activated receptor-γ, CCAAT/enhancer–binding protein α, and fatty acid–binding protein 4 expression in mouse embryonic fibroblasts. Constitutive Nrf2 activation inhibited lipid accumulation in white adipose tissue, suppressed adipogenesis, induced insulin resistance and glucose intolerance, and increased hepatic steatosis in Lep(ob/ob) mice.